A surprising lack of consequences when constraining language - Vaughan-Johnston, Thomas Ian; Nguyen, Andrew; Jacobson, Jill A. (Frontiers in Social Psychology, 2024)
Labels considered normatively appropriate for specific social identity groups change. Researchers have examined the effects of censorship and slur usage, but minimal research examines the psychological consequences of imposing new language constraints on people. Across four samples of university students (Ntotal = 997), we sought participants’ compliance in avoiding usage of numerous commonplace group labels while they wrote essays about obese people (Sample 1) or specific ethnic groups (Samples 2-4). We observed consistently high compliance rates: participants either invented novel terminology to describe the group or avoided group labels entirely. We observed a substantial absence of task discomfort, attitudinal shifts towards the group, or motivational shifts, according to Bayesian analyses. Nor did we detect negative effects of language constraint among people who saw themselves as opposed to censorship. Although free speech and respectful language remains a multifaceted social debate, our findings show that university students are willing to follow even completely contrived language directives when describing social identity groups and to do so without substantial discomfort or backlash against those groups.